The Relationship Between Learning Styles and Cognitive Competencies in Biology Learning - Winalda, Egatri; Ristiono, Ristiono (Thinking Skills and Creativity Journal, 2022)
The problem often faced in the learning process is the low learning outcomes obtained by students. One of the factors that influence student learning outcomes is learning style. The observations show that teachers rarely use varied learning methods, models, and media. At the time of learning, each student did not understand their learning style (modality). It can cause an imbalance between students' learning styles and the models, methods, or learning media used by the teacher, causing low cognitive competence in students. This study analyzes the relationship between students' learning styles and cognitive competence. This research is a descriptive study. The total sample is 121 students—data collection techniques using learning outcomes tests, questionnaires, and documentation. Data analysis in this study used the Pearson Product Moment correlation formula. Correlation testing is done by using the t formula to determine whether the correlation coefficient is significant or not. The percentage contribution of students' learning styles on students' cognitive competence was analyzed using determinant coefficients. Based on the research that has been done, it is found that there is no significant correlation between learning styles and students' cognitive competencies. The dominant learning style is the visual learning style, then the kinesthetic learning style, and the least is the auditory learning style. This study concludes that there is no significant relationship between learning styles and students' cognitive competencies.